Propagation of spherical shock waves in a contiguous elastic-plastic environment (Международный научный журнал «Инженер», 2026)
This article studies the propagation of one-dimensional spherical shock waves in a homogeneousmedium, represented by soil or ground, modeled as a continuous elastic-plastic medium. The researchassumes that the loading shock waves in the elastic-plastic medium filling the surrounding spacepropagate at a constant velocity. Furthermore, the effective use of directional blasting technology inconstruction, mining-geological industries, and other technical fields requires determining the relevantmechanical parameters of continuous elastic-plastic media subjected to shock loads. Within the theory ofsmall elastic-plastic deformations, the relationship between the components of the stress and straintensors in a spherical coordinate system is taken into account.